Social - Local - Mobile: The Future of Location-based Services - Heinemann, Gerrit (Springer, 2015)
n the future, shopping will be greatly influenced by a combination of localization issues, mobile internet at the point of sale, and use of social networks. This book focuses on the ‘SoLoMo synergies’ that arise from this paradigm shift in future shopping, which also promises new and effective marketing options for traditional retailers. It also reflects the current status of research and business practice, analyzing the basic factors of SoLoMo in detail. The importance of Location-based Services (LBS) is elaborated and analyzed in an empirical study using a market based case of kaufDA – a leading German online shopping network. The evidence shows that customers see LBS as an attractive tool and are prepared to change their buying behavior. Though LBS is still in its early stages and its professional longevity remains to be seen, it also promises tremendous potential for the future.